IMPLEMENTASI PEMBERIAN REWARD DALAM MENINGKATKAN MOTIVASI BERPRESTASI GURU SDN 007 KUNTO DARUSSALAM - Syafrida Syafrida (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to determine whether achievement motivation can be improved through the award of SDN 007Kunto Darussalam. Based on the description on the background, problem identification and problem restriction,the focus of this research is related to the effort to improve the achievement motivation of the teacher throughthe giving of reward at SDN 007 Kunto Darussalam. The School Action Research was conducted only at SDN007 Kunto Darussalam. In one supervision of the researcher himself. This type of research is a School ActionResearch (PTS) located at SDN 007 Kunto Darussalam, which is aimed at teachers. The main reason is from theobservation and information from the teacher, that the motivation to teach the teacher is still classified as less.The sample in this study is all teachers in SDN 007 Kunto Darussalam amounted to 12 people. Based on theabove data can be seen, that the motivation to teach teachers can be improved through the provision of rewards.Aspects of reward given by the tutor is known that from cycle I increases in cycle II. If the cycle I get a score of20 then the second cycle is better to get a score of 32. On the aspect of achievement motivation teachersobtained in the first cycle of 56% with good enough category and on the second cycle increased to 81% withvery good category.